Application of Gold Nanorods for Photothermal Therapy - Chuanzhi LIU; Ping GONG; Yuping LIANG; Zuobin WANG; Li WANG (Medžiagotyra)
Photothermal therapy is a treatment method which used a material with a high conversion efficiency of field or biological synthetic material, using target recognition technology gathered near the cancer tissues after injected into human bodies, with near-infrared convert light energy into heat energy to kill cancer. Here reported the biocompatible use of gold nanorods(GRNs) as probes for cancer targeting in vitro. More specifically, this paper demonstrated a progressive synthesis approach in fabricating water-dispersible gold nanorods. These nanorods were prepared by replacing cetyltrimethylammonium bromide with a mixture of 15-polypeptide(15P) molecules, such that a variety of cell viability assays did not reveal any signals of toxicity in the treated cells. The samples size was estimated to be 70-80 nm; Dynamic light scattering reveals that the cores of the gold nanorods are protected from the outside environment by the 15-polypeptide. Photothermal treatment indicated that 15P-GNRs can stain tumor growth and devoted the pivotal steps in promoting of the use of ternary GNRs as a tumor targeting, more importantly, these results suggest that 15P-GNRs can serve as biocompatible synthetic material and multimodal platform for various bio-applications and the micelle-encapsulated nanoparticles formulation was able to target the tumor site directly. On the other hand, Photothermal therapy has great effect in killing cancer cell with near-infrared.